The Implementation of STEM-Based Discovery Learning Model in Motion Systems Concept to Improve Learning Outcomes - fadlina fadlina; Soleh Ritonga (Universitas Syiah Kuala, 2021)
The learning outcomes of students in class 11th Islamic Senior High School Banda Aceh are still low, the low learning outcomes of students in learning the motion system concept in class 11th Islamic Senior High School Banda Aceh are due to the teaching and learning process using practicum equipment on the concept of inadequate motion systems, this is evidenced by the laboratory space untapped and incomplete equipment. So that students are more likely to learn only from handbooks without direct learning experiences in real lifeThe research approach used is quantitative with the type of pre-experimental research, the research design used is the One-Group Pretest-Postest Design. The population of the study was all students of class 11th, amounting to 292 people. The sampling technique used was total sampling, the sample in this study consisted of 292 students. Pretest and Posttest questions in the form of reasoned choice test questions are used as instruments to measure learning outcomes. Data analysis consisted of normality test, paired sample t-test and N-gain test at a significant level of 0.05. The results of the paired sample t-test obtained ρ .001, so it was concluded that there were differences in student learning outcomes before and after learning with the application of the STEM-based Discovery Learning model on the motion system material in Islamic Senior High School 1 and Islamic Senior High School 2 Banda Aceh City. The results of the N-gain test using the Meltzer formula, the n-gain of learning outcomes obtained is 0.50, so the increase in student learning outcomes is in the moderate category.